Is there progress in the adsorbent development for water treatment? - Tero Luukkonen; Juhani Teeriniemi (iScience, 2025)
Summary: Adsorption technology is an essential part of modern water treatment. However, only a handful of adsorbent materials are used industrially, which is in striking contrast with the exponentially increasing scientific publishing activity. In this perspective, the aim is to discuss the global progress on the adsorbent materials development by using the reported adsorption capacities as a simple probe. An automated text analyzer employing a large language model was used to extract adsorption data. Total 11,664 scientific journal articles about ammonium, arsenic, lead, methylene blue, or nitrate adsorption covering years 1973–2023 were analyzed. When the adsorption capacities were plotted as a function of the publication year, a two-fold trend was revealed: most of the studies (i.e., up to the 50–75% percentile ranks) revealed none or only modest improvement in the adsorption capacities, while the very best materials exhibited staggering capacities up to the order of 103–104 mg g−1.